2019
DOI: 10.1002/cbin.11135
|View full text |Cite
|
Sign up to set email alerts
|

The absorption of apolipoprotein E by damaged neurons facilitates neuronal repair

Abstract: Traumatic brain injury (TBI) is one of the common diseases diagnosed in departments of neurosurgery. Apolipoprotein E (apoE) can improve the prognosis of TBI. In this study, we aimed to explore the effect of apoE in mechanically damaging neurons as well as its underlying molecular mechanism. Western blot analysis and immunofluorescence assay was performed to detect the expressions of associated proteins. The expressions of apoE, p38, and phosphorylation of P38 were increased in mechanically injured neurons com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…APOE has been shown to regulate microglial phagocytosis via TREM2 35 , 46 . During ischemic stroke, APOE is not synthesized by neuron and its expression in astrocytes and microglia increases 30 .…”
Section: Discussionmentioning
confidence: 99%
“…APOE has been shown to regulate microglial phagocytosis via TREM2 35 , 46 . During ischemic stroke, APOE is not synthesized by neuron and its expression in astrocytes and microglia increases 30 .…”
Section: Discussionmentioning
confidence: 99%
“…[ 29 ] Researches on brain neurons have shown that APOE affects the growth and regeneration of axons in vitro through MAPK signaling pathways, [ 30 ] and injured neurons can absorb and secrete APOE to promote neuron repair by activating MAPK signaling pathways. [ 31 ] In addition, studies have shown that the metabolic regulation of APOE in human liver cells is affected by interfering MAPK/extracellular regulated protein kinases (ERK) signaling pathway, [ 32 ] and APOE stimulates the survival of neural stem cells through regulating MAPK/ERK signaling pathway. [ 33 ] Since APOE is related to the ERK signaling pathway, can APOE affect EC metastasis through the ERK signaling pathway?…”
Section: Discussionmentioning
confidence: 99%
“…Many foreign reports have shown that dyslipidemia often develops in patients with long-term consequences after TBI [1,5,6,13,14,16]. Changes in lipid spectrum may be explained by the fact that neurotrauma itself leads to a decreased rate of lipid decomposition due to reduced activity of lipoprotein lipase enzyme associated with decreasing rate of total cholesterol clearance [2, 14,15,20].…”
Section: оригінальні дослідження Original Researchesmentioning
confidence: 99%
“…According to numerous literature data [1,2,5,6,10,11], neurotrauma itself may lead to the development of dyslipidemia due to the increased lipid degradation. Some authors showed that in children dyslipidemia was one of the main trigger factors that caused some metabolic syndromes [4].…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation